ANALISIS DINAMIK RESPON STRUKTUR GEDUNG BERATURAN DAN KETIDAKBERATURAN HORIZONTAL - Ummi Khoirunnissa; Rinawati Djakfar; Yanuar Setiawan (Politeknik Negeri Jakarta, 2020)
Indonesia is a country with geographical location where 4 large tectonic plates meet. Therefore, if a collision or frictionhits the country, it is vulnerable to earthquakes. This condition makes the buildings more vulnerable to earthquakes. The effect of earthquake force and the performance of the resulting structure will be different if the same load is applied to a regular building and to an irregular building. The method to calculate the effect of the earthquake on the analysis of high-rise building structures in this study used dynamic analysis with spectrum response referred to SNI 03-1726-2012 and 2013 ETABS software program assistance (13.1.1 build 1035). This study aimed to compare the performance of the structure based on the deflection value and the story drift limits in regular and irregular buildings. In this study, the response of structural performance on three building models was calculated with variations in horizontal structure irregularity and then the results were compared. In this research, the biggest deflection was resulted on the re-entrant corner irregularity model C in the x-direction of 7,219 mm and the y-direction of 4,244 mm. Based on the deflection value in the x-direction and y-direction on all building models, the story drift due to the effect of the earthquake plan was less than Delta-a, wherein this study obtained Delta-a by 80mm, so it could be concluded that it was safe against the story drift limits in SNI-03-1726-2012. Keywords: Spectrum Response, Deflection, Horizontal Irregularity.